A inclusão digital das pessoas idosas: um olhar sobre o campo da ciência tecnologia e sociedade - Orlandi, Brunela Della Maggiori (2018)
Introduction: Just as human aging has been happening rapidly and progressively, so has information and communication technologies. This indicates to us that different studies and interventions need to happen so that the part of the population with 60+ years, denominated digital immigrants, do not stay in the margin in this process. One of the fronts is in the field of Gerontology, allied to the Field of Science, Technology and Society, which show great importance in contributing to the effective contemplation of this process, thus proposing new conceptions of learning throughout the aging process. Objectives: Identify and characterize existing Digital Inclusion programs in Brazil and Portugal aiming to propose a format to teach technology to 60+ year olds. The study also aims to identify the profile of the elderly users of the Digital Inclusion programs and their vision on the learning process of digital technologies. Method: Through technical visits to the institutions in both countries, the work was carried out, in relation to the collection of data, in two stages: i) the research sites were first surveyed, being in Portugal Universities of the Third Age and in Brazil linked institutions to the public sector; ii) the application of semistructured questionnaires to the coordinators and/or teachers of the institutions investigated, as well as a semi-structured questionnaire for 60+ year old participants in digital inclusion activities. The results were analyzed according to Bardin’s content analysis and by simple statistics. Results: In total 23 institutions participated, being 11 in Brazil and 12 in Portugal and 44 60+ years people, being 28 from Brazil and 16 from Portugal. We can observe an ideal structuring intention for the offer of teaching activities to the technologies by both countries and many similarities in the responses of the investigated population with 60+ years regarding the learning process, however when crossing the information between coordinators and/or teachers with the information of 60+ year olds, we noticed that there are problems in the communication between both, affecting the way the teaching-learning process occurs. Conclusion: We can identify that there are activities to promote learning in technologies, but we can not infer that there is a digital inclusion of these 60+ year olds in both countries. Considering the answers by both groups investigated, the work presents an ideal format of courses that offer activities with the intention to include people with 60+ years in the digital era. Thus, the need to development of a way to teach the use of the technologies to 60+ year olds becomes evident with this work.